VEŽBANJE KAO FAKTOR MODIFIKACIJE NIVOA KORTIZOLA - Biljana Vitošević; Tatjana Popović-Ilić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Cortisol is a glucocorticoid hormone secreted from the adrenal cortex and it represents a key component of the hormonal hypothalamic-pituitary-adrenal axis. The best-known metabolic effects of cortisol on the metabolism are the stimulation of gluconeogenesis, increased protein catabolism and increased lipolysis. Exercise is considered as a specific stressor that can modify the cortisol levels in the human body. The intensity and duration of exercise are factors that determine the response of cortisol. This article is a brief review on the effects of the cortisol responses at different intensity of exercise, its relationship with testosterone and highlights the importance of its role as a hormonal component of adaptation of the organism to exercise that preserves and protects the body from the negative physiological consequences.